The role of federalism in developing the US during nineteenth-century globalization - Eric Rauchway (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
During its development into a continental empire, the US, like other countries relied on the investment of capital and labour from abroad; unlike other countries, the US had a peculiar political institution, federalism, which channeled these resources and also determined the course of protest against these resources. The paper argues that federalism played a key role in determining the course of US economic development and reaction to this early instance of globalization, a role with possible lessons for other countries today. – federalism ; globalization ; development ; United States
Keywords: N21; N41; N91; 330